LANDSLIDE CHARACTERISTICS FROM CONCEPTUAL MODELLING OF WEATHERED LAYERS USING SUBSURFACE RESISTIVITY IN SANGON, DIY - Lutfiana, Hilma; Giamboro, Wrego Seno; Hidayat, Wahyu; Sukmawan, Dwi Indra (Engineering Faculty Universitas Lampung, 2025)
The Sangon area is located in Kulonprogo Regency, which physiographically has landforms in the form of hills and mountains. Steep slope angles of the hills and weathered surface rock conditions increase the potential for landslides hazard in the Sangon area. This study aims to identify unstable layers that are prone to landslides in the Sangon, Kokap, and Kulonprogo areas. Information regarding the potential characteristics of landslides can significantly impact reducing losses caused by landslides hazard. Conceptual modelling of weathered layers that have the potential to trigger landslides has been carried out in the research area using resistivity distribution data of subsurface rocks using the geoelectrical method. Geoelectrical data from five measurement lines with a length of 290 m each line with a southeast-northwest orientation can delineate an image of the distribution of weathered layers in the subsurface. Based on the results of two-dimensional (2D) subsurface resistivity inversion modelling, it is known that the weathered layer as soil form andesite rock has a low resistivity value with a range of 7 m – 246 m with a depth of 0 - 12 meters in the subsurface. The distribution of resistivity value of the weathered layer is depicted in the 3D model to determine the distribution of the weathered layer, which is then made into a conceptual model that can describe the characteristics of landslides. The description of the 3D resistivity model of subsurface rocks produces a conceptual model of landslides in the research area, where the potential for landslides that may occur has characteristics in the form of debris flow or translational. The unstable layer volume was 947,000 m³, with a slope gradient ranging from 19% to 35%, with a moderate to steep slope.